Web-Based Sales Forecasting Point-of-Sales System Using Simple Moving Average Method at Haka Farma Pharmacy - Rifqi Herlambang; Dendy K Pramudito; Ernanto (Jurnal Informatika Ekonomi Bisnis, 2026)
POS-POS system is a POS which manages sales transactions, inventory, and daily sales reports at Haka Farma Pharmacy, but it has no sales forecasting capacity. Therefore, many judgment and judgment making processes often need to go through previous procurement to determine the inventory stocks. In order to resolve this issue, this study was aimed at creating a web-based POS system in combination with a sales forecasting component in conjunction with a simple moving average module. Development of the system is conducted using waterfall, which involves requirement analysis, system design, implementation, testing, and deployment of the system. The techniques employed were observational, staff interviews through pharmacy members, and through in-depth literature review. The system developed in PHP using the Laravel framework, was implemented through the MySQL database managers for system. The software's forecast module also uses SMA method to calculate the average sales volume over the last three months in order to estimate demand in the future. Functions testing and testing of system: user authentication, product management, sales transaction processing, reporting, forecasting, and error analysis were done. Testing results were not inconsistent with the specification; all the system related features were functioning as expected. From paracetamol sales data, we found a 253-unit rate expected for December 2025. The MAPE data shows strong forecasting in the form of 3.16% MAPE (Mean Absolute Percentage Error) indicating its predictive power in this study. This confirms that the developed forecasting module can assist in inventory planning, reducing uncertainty for all decision makers, and optimize operational efficiency with evidence-based control of stock in Haka Farma Pharmacy.